Understanding the challenges of deploying a milestone-tracking application in a cross-cultural context. Issue 162 (June 2022) - Escobedo, Lizbeth; Arriaga, Rosa I.
Highlights: Mobile applications are a useful tool for parents to monitor developmental milestones of children, and could help to detect developmental issues and act early. The ActEarlyMEX tool is a useful tool for essential tracking activities, and it provides educational insights into parents child's development. The design of tools for parents to monitor developmental milestones should consider including facilitating tracking among multiple multigenerational caregivers; developing sensors that track the child's behavior and automatically updates relevant milestones and generally streamline milestone tracking for busy parents. Abstract: Actively tracking children's developmental milestones can alert caregivers to possible developmental delays. However, this can be difficult since there are only a few resources that provide reliable and culturally sensitive references for tracking and logging developmental progress. To address this issue, we adapted the milestone-tracking mobile application of the Centers for Disease Control and Prevention for Mexican-Spanish-speaking individuals and called it ActEarlyMEX. We conducted both a usability study (including two culturally different cohorts) and a two-month deployment study to understand milestone-tracking behavior in the real world. The usability study helped us create a culturally relevant app that we evaluated in the deployment study, in which we recruited 24 participants (18 parents and 6 family members) from a local day care center. The results showed that ActEarlyMEX provided participants with insights into age-appropriate developmental milestones. The participants also indicated that multiple caregivers should be allowed to simultaneously use ActEarlyMEX and that there should be a feature that automatically updates relevant milestones based on a child's behavior. The results also provide insights for researchers that investigate culturally situated health informatics and define a set of design guidelines for studying milestone tracking.